Key Industrial Sectors In The Sulampua Area As A Result Of Nusantara Capital City Development - Ernawati, Ernawati; Ilyas, Ilyas; Asri, Mansyur (LPPM ISNJ Bengkalis, 2024)
This study aims to determine the sectors that need to be developed in the non-golden triangle area of the SULAMPUA region as a result of the Nusantara Capital City (NCC) development. Descriptive research is being conducted utilizing secondary data from Statistics Indonesia’s 2016 IRIO (Inter-Regional Input-Output) table. The IRIO model is used in data analysis for 20 secondary sub-sectors. The SULAMPUA region comprises 10 provinces, with the Golden Triangle region comprising South Sulawesi, Central Sulawesi, and West Sulawesi. The study results show that to take advantage of opportunities for the development of NCC, several key industries need to be developed for non-golden triangle areas, namely the food industry (I-13), non-metallic mineral goods industry (I-21); other processing industries, machinery and equipment repair and installation services (I-27); and the wood industry, goods from wood and cork, and woven goods from bamboo, rattan, and the like (I-17). Maluku, Papua, and West Papua provinces have relatively little opportunity to develop the industrial sector and benefit from moving NCC. Because the sectors connected directly or indirectly and the key sectors of these three provinces are capital-intensive industries, MSMEs have more significant barriers to entry. This research can be a reference for local governments in exploring potential industrial sectors to be developed to achieve NCC development opportunities.